Effects of Teaching Paraphrasing Skills to Students Learning Summary Writing in ESL - Siew Chee Choy; Mun Yee Lee (University of Windsor, 2012)
This study examines the effects of teaching paraphrasing skills to students of tertiary level on summary writing. Other studies have found that students have limited paraphrasing skills that they can use to help them complete a task. Other factors like culture may also play a part. Twenty two students of lower intermediate level of proficiency in English were used in the study. A piece of summary writing task requires critical thinking skills to produce effective and concise writing. The nature of the task is basically constructing a general conceptual framework from the analysis of the passage and synthesis of specific information from it. This study analyses perceptions of students when handling a summary writing and the awareness of their learning and thinking. Inquiry-based learning (IBL) is used as a strategy to encourage independent thinking when doing summary writing in the classroom. The students in the study found the skills taught to them useful and they were able to apply them in a limited way. Added to this the results from the study indicated that the skills did not help the students equally. Students' perception of their confidence in their learning abilities and the task assigned may not accurately reflect their paraphrasing skills.